2008
DOI: 10.1007/s10499-008-9193-7
|View full text |Cite
|
Sign up to set email alerts
|

Best among unequals? Effect of size grading and different social environments on the growth performance of juvenile Atlantic halibut

Abstract: In order to study the effect of rearing juvenile halibut in different social environments, individually tagged juvenile halibut were size-graded into two size classes (Large, L, and Small, S) with ungraded fish as control. After ca 6 weeks, the two sizegraded groups were again graded into two size classes creating four experimental groups: Large of the Large (LL), Small of the Large (SL), Large of the Small (LS), and Small of the Small (SS). Grading (overall mean of the four grading groups) improved growth rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The CV W values for the 9 cohorts studied (30 to 55%) were comparable to the CV W values reported for other species at a similar life stage (Folkvord & Otterå 1993, Sakakura & Tsukamoto 1998, Baras et al 2000, Imsland et al 2009); therefore, the sample size estimates from the current study can act as a guideline for researchers who would like some assurance that they have adequately sampled juvenile populations in order to gain a repeatable average size measurement.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The CV W values for the 9 cohorts studied (30 to 55%) were comparable to the CV W values reported for other species at a similar life stage (Folkvord & Otterå 1993, Sakakura & Tsukamoto 1998, Baras et al 2000, Imsland et al 2009); therefore, the sample size estimates from the current study can act as a guideline for researchers who would like some assurance that they have adequately sampled juvenile populations in order to gain a repeatable average size measurement.…”
Section: Discussionsupporting
confidence: 78%
“…The size variance of newly hatched marine fish larvae is relatively low (coefficient of variation of weight, CV W : 8 to 20%; Kestemont et al 2003); and a normal distribution is a reasonable approximation of the size distribution. However, the highly variable growth rates of larvae or juveniles mean that cohorts often develop into skewed size distributions, with CV W values typically in the range of 20 to 50% or higher (Folkvord & Otterå 1993, Baras et al 2000, Moran 2007, Imsland et al 2009). The variable and skewed distributions of juvenile fish prevent the use of standard error minimization and power analysis to assess the effect of sample size on estimation accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Growth rate is therefore an important determinant of the probability of individual survival and is often used as a fitness proxy (Brown, Jones, & Braithwaite, ). Experimental studies on several fish species have revealed growth differences relating to foraging activity (Imsland, Jenssen, Jonassen, & Stefansson, ; Jobling & Baardvik, ; Martin‐Smith & Armstrong, ). Studies on rainbow trout Oncorhynchus mykiss have demonstrated that individuals taking greater risks while foraging grew faster, but survived at a lower rate in the presence of predators than individuals taking fewer risks (Biro, Abrahams, Post, & Parkinson, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in Japanese flounder Paralichthys olivaceus , small fish grew better when reared alone than in unsorted groups while the growth of large fish was not affected (Dou et al, ). Moreover, in Atlantic halibut Hippoglossus hippoglossus (Imsland et al, ) and Arctic charr Salvelinus alpinus (Baardvik & Jobling, ), growth was better for both size classes when reared together compared to rearing each size class alone. Although similar comparisons for European seabass cannot be easily performed [Petroviĉ et al () focused on the graded groups without keeping an ungraded group for comparison and in Papadaki et al () fish sex was implicated in growth effects of grading], it seems that grading effects are species specific and probably related to the specific body mass examined.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been observed that grading did not affect growth performance in several fish species (e.g., Anoploma fimbria, Sogard & Olla, 2000; Bidyanus bidyanus, Barki, Harpaz, Hulata, & Karplus, 2000;Polyodon spathula, Onders, Mims, & Dasgupta, 2011;Clarias gariepinus, Martins, Aanyu, Schrama, & Verreth, 2005; Siganus rivulatus, Ghanawi, Saoud, & Shalaby, 2010; Solea senegalensis, Salas-Leiton, Anguis, Rodríguez-Rúa, & Cañavate, 2010). Some fish species [e.g., Hippoglossus hippoglossus (Imsland, Jenssen, Jonassen, & Stefansson, 2009)] showed increased overall growth rate when reared in the ungraded groups. Besides, in some cases, grading seems to be beneficial only for fish of a specific body mass.…”
Section: Introductionmentioning
confidence: 99%